2022
DOI: 10.1093/ajhp/zxac046
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evaluation of insulin requirements after GLP1 agonist or SGLT2 inhibitor initiation and titration

Abstract: Disclaimer In an effort to expedite the publication of articles, AJHP is posting manuscripts online as soon as possible after acceptance. Accepted manuscripts have been peer-reviewed and copyedited, but are posted online before technical formatting and author proofing. These manuscripts are not the final version of record and will be replaced with the final article (formatted per AJHP style and proofed by the authors) at a later time. Purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…Furthermore, 48.3% of patients were able to discontinue insulin therapy entirely following the initiation of 1 or both agents. This contrasts with the studies by Van Dril et al 5 and George et al 6 who found that patients’ insulin dosage may be decreased but did not note insulin discontinuation.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Furthermore, 48.3% of patients were able to discontinue insulin therapy entirely following the initiation of 1 or both agents. This contrasts with the studies by Van Dril et al 5 and George et al 6 who found that patients’ insulin dosage may be decreased but did not note insulin discontinuation.…”
Section: Discussioncontrasting
confidence: 64%
“…While studies indicate the potential for decreased insulin use with these medications, there is a gap in exploring complete discontinuation. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%